IDENTIFICATION FUNGI OF GOLDFISH (Carrasius auratus) TRADED ON TAMPAN SUB-DISTRICT PEKANBARU CITY BY Polymerase Chain Reaction (PCR) METHOD - Rebeka Valensia; Henni Syawal; Iesje Lukistyowati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT            Fungal infections is one of the secondary infectious that can reduce the aesthetics value of goldfish, and cause 50% death in goldfish. The objective of the study was to find out the species of pathogenic fungi in goldfish. the method used was survey at the location of the Delima village, Tuah Karya village, Simpang Baru village, Tampan Sub-District, Pekanbaru City. The fish used were 7 - 12 cm as many as 27 tails. Conventional identification includes macroscopic inspect of fungi colonies and inspect microscopic of fungi hyphae. Molecular identification was carried out by Polymerase Chain Reaction (PCR) technique and analyzed with Bioedit, BLAST and MEGA applications to find out the phylogenetic tree. Research parameters include water quality and fungi prevalence. The results of conventional identification techniques found the species of fungi, includes Aspergillus niger, Penicillium sp., Curvularia sp., Bipolaris sp., Fusarium sp. The result of molecular identification techniques found the species of fungi, includes Aspergillus tamarii with homolog value 99%,Fungal endophyte with homolog value 98%, Curvularia pseudorobusta with homolog value 93%. The conclusions obtained from this study are Fusarium sp. and Curvularia sp. The prevalence value in the second sampling with an average of 66.33% was higher than the value of the first sampling with an average 22,22% and third sampling with an average 11,11%. Keywords:Fungi, Carassius auratus, Polymerase Chain Reaction